Multiple relapses of hyperthyroidism after thyroid surgeries in a patient with long term follow-up of sporadic non-autoimmune hyperthyroidism - (:unkn) unknown (JOHANN AMBROSIUS BARTH VERLAG MEDIZINVERLAGE HEIDELBERG GMBH, 2008)
Constitutively activating thyrotropin receptor (TSHR) germline mutations have been identified as a molecular cause of congenital hyperthyroidism. Patients with relapsing hyperthyroidism were previously treated with surgery and radioiodine. We report on a 22 year old male patient who was treated for his multiple relapses of hyperthyroidism by repeated subtotal thyroidectomies (STE). During the 22 years of follow-up, the patient developed several relapses of hyperthyroidism, four of them after thyroid surgeries. Sequencing of the TSHR gene revealed a gain-of-function mutation with an amino acid exchange of aspartate to tyrosine in codon 633 which is located in the sixth transmembrane domain of the TSH receptor. The absence of the mutation in all other family members identifies the patient's TSHR mutation as a sporadic germline mutation. In this patient, thyroid tissue growth and hyperthyroidism could repeatedly be controlled only for limited periods by near total thyroidectomy. Therefore, this case confirms that early combined treatment with near-total thyroidectomy plus radioiodine therapy seems to be the treatment of choice for patients with sporadic non-autoimmune hyperthyroidism.
Keywords: thyrotropin; hormones; receptors; signal transduction; sporadic germline mutation; non-autoimmune hyperthyroidism; THYROTROPIN-RECEPTOR GENE; STIMULATING HORMONE-RECEPTOR; GERMLINE MUTATION; CONGENITAL HYPERTHYROIDISM; TSH RECEPTOR; NONAUTOIMMUNE HYPERTHYROIDISM; CONSTITUTIVE ACTIVATION; EXTRACELLULAR DOMAIN; SOMATIC MUTATIONS; IDENTIFICATION